2007
DOI: 10.1097/cji.0b013e318158fcff
|View full text |Cite
|
Sign up to set email alerts
|

Immunization With a Recombinant MAGE-A3 Protein After High-dose Therapy for Myeloma

Abstract: MAGE-A3 is frequently expressed in high-risk multiple myeloma (MM). We immunized a healthy donor with MAGE-A3 protein formulated in AS02B to transfer immunity to her identical twin, diagnosed with MAGE-A3-positive MM. After a melphalan 200 mg/m syngeneic peripheral blood stem cell transplant, primed donor cells collected after immunizations were transferred and followed by repeated patient immunizations. MAGE-A3 immunizations were well tolerated. Strong MAGE-A3-specific antibody, cytotoxic T-lymphocyte (CTL), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…39,49 This phenotype has been reported on Melan-A and tyrosinase tumorreactive CD8 ϩ T cells in melanoma patients 40 and indicates that CTAg-specific CD8 ϩ T cells appear to be prevented from interacting with tumor cells in vivo. This is supported by the finding that such clones revert to CD45RO expression after stimulation with antigen in vitro, and a recent study showed that MAGE-A3 vaccine-induced CD8 T cells expressed a CD45RO 25 phenotype in vivo. The physiologic mechanisms behind these observations are uncertain but could potentially be related to the increase in T-regulatory cells that has been observed in MM, or a lack of appropriate costimulation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…39,49 This phenotype has been reported on Melan-A and tyrosinase tumorreactive CD8 ϩ T cells in melanoma patients 40 and indicates that CTAg-specific CD8 ϩ T cells appear to be prevented from interacting with tumor cells in vivo. This is supported by the finding that such clones revert to CD45RO expression after stimulation with antigen in vitro, and a recent study showed that MAGE-A3 vaccine-induced CD8 T cells expressed a CD45RO 25 phenotype in vivo. The physiologic mechanisms behind these observations are uncertain but could potentially be related to the increase in T-regulatory cells that has been observed in MM, or a lack of appropriate costimulation.…”
Section: Discussionsupporting
confidence: 68%
“…Given the potential role of CTAgs as targets for immunosurveillance and immunotherapy strategies, it is essential to understand the cellular and humoral immune responses to these proteins in MM and MGUS to maximize tumor-specific immune responses. 6 Indeed, both NY-ESO-1-based immunotherapy using protein transduction of dendritic cells 24 and MA9E-A3 protein immunizations 25 are being developed in multiple myeloma patients.…”
Section: Introductionmentioning
confidence: 99%
“…As these genes are only expressed in 13% to 28% of patients, they are ideal targets for personalized treatment, for example, add-on for current induction treatment regimen, and respective clinical trials are in preparation. GEP likewise allows the screening for a large number of immunotherapeutic targets, for example, cancer testis antigens (18,50), exemplified by MAGEA3 (18,19). In both cases GEP-R easily allows assessment of expression of such target genes, thus enabling personalized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,17), and potential targets of vaccination strategies (e.g., MAGEA3; refs. 18,19). GEP can currently be done in about 80% of therapy requiring patients in terms of available material, that is, purified myeloma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another study 50 demonstrated significant CTA-specific immune responses in a cohort of 41 patients who underwent allogeneic stem cell transplantation for the management of acute myeloid leukemia or MM. In one study, 51 immunization of a healthy donor with defined CTA protein led to generation of an antimyeloma response in MAGE-A3 þ MM. The donor was immunized with MAGE-A3 protein, and primed donor cells collected after immunization were transferred to her identical twin after syngeneic stem cell transplant, followed by repeated patient immunizations.…”
Section: Cancer/testis Antigens As Csc Immunotherapy Targetsmentioning
confidence: 99%